PROSA LIRIK CALON ARANG KARYA TOETI HERATY: STUDI DEKONSTRUKSI - Widowati Widowati (CARAKA, 2015)
This research aimed to describe the reading process of lyric prose titled Calon Arang by Toeti Heraty based on Jaques Derrida’s Deconstruction theory. This study is a qualitative research. The data of this research were unit of events which were conveyed in the form of row and line. The resource of the data was Calon Arang prose lyric text. The research instrument was the writer’s ability to analyze the data that were got with the concepts and theories related to Jaques Derrida Deconstruction. Method of collecting the data used was qualitative, while the techniques were observation and note-taking. The data analysis used in this research was descriptive analysis method, while the analysis technique used was descriptive qualitative technique. The result of this study showed that, 1) lyric prose titled Calon Arang was written based on the manuscript of editing by I Made Suastika from the manuscript numbered LOR 5387/5279, written on palm leaves, in ancient Javanese language, in 1462 of Saka year (1540 Masehi), 2) based on Deconstruction reading, there were 34 units of opposition which were explicit and 7 which were implicit. Hierarchy trace showed that there were two big oppositions; they were winning opposition unit and defeat opposition unit. Calon Arang’s defeat was used as the base to describe the woman oppression based on cultural patriarchal system. The women oppression covered oppression in reproduction aspect, advertising and beauty which reflected full patriarchal system, capitalism and hedonistic lifestyle.